Implementation of the Snowball Throwing Learning Model with Ice Breaking in Mathematics Subject - Hiyum, Ervinia Risti Waning; Nugroho, Arya Setya; Yunita, Nourma (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
Through the use of the snowball tossing learning model with ice cracking, this study seeks to increase the interest and learning results in mathematics among grade V students at UPT SD Negeri 5 Gresik during the 2024–2025 academic year. The planning, execution, observation, and reflection phases are all included in this two-cycle classroom action research project. Twenty-seven grade V students from UPT SD Negeri 5 Gresik served as the study's subjects. The study's findings demonstrated a notable improvement in student learning outcomes. The learning completion rate in cycle I was barely 10%, whereas the average student score was 66.66%. The average score rose to 96.30% in cycle II, and 97% of the students completed the course. Furthermore, there was an increase in the development of learning interest. The student learning interest questionnaire's average score in cycle I was 54%, falling into the poor group; in cycle II, it rose to 90.5%, falling into the adequate category. Thus, cycle II has seen the achievement of the success indicator.